National School Feeding Program (PNAE): experience of purchasing products from family farmers for school feeding in Vila Velha-ES - Espolador Leitão, Ana Letícia; Venturim Bernardino, Renata (Geografares, 2018)
In this paper, we highlight the importance of public policies that encourage the direct purchase of agricultural products from family farmers. Through an exploratory research, we sought to verify the implementation of the National School Feeding Program (PNAE) in the municipality of Vila Velha from 2012 to 2015, through bibliographical, documentary and empirical research. Our results point that Vila Velha stands out in the receipt of financial resources for this purpose, although there are challenges in its operationalization regarding intersectorality, regularity in the supply of foodstuffs and the development of educational work in schools.Keywords: Family Farmers, Public Policies, Programa Nacional de Alimentação Escolar (PNAE).